- #1

- 198

- 0

## Homework Statement

(2x - y) + (2y-x) dy/dx = 0

y(1) = 3

Solve and determine where the solution is approximately valid.

## Homework Equations

## The Attempt at a Solution

Ux = 2x - y

Uy = 2y - x

U = x^2 - yx + h(y)

Uy = 2y -x = -x + h'(y)

h'(y) = 2y

h(y) = y^2

x^2 - yx + y^2 = c

1 - 3 + 3^2 = c = 7

I'm not really sure where to go from here,

x^2 - yx + y^2 = 7

However, the answer is quite a bit different:

y = x + sqrt( 28 - 3x^2)/2 and I can't quite see the step toward that. (x-y)^2 = 7-xy but I still can't seem to solve for y

Last edited: